Management and cost accounting - Bhimani, Alnoor (Financial Times/Prentice Hall, 2012)
Includes European and Harvard Business School cases, this book has been adapted to suit a UK/European syllabus. The Euro is used as the reference currency throughout the text, whilst a range of individual currencies are used in the questions